2015
DOI: 10.18869/acadpub.pbr.1.1.32
|View full text |Cite
|
Sign up to set email alerts
|

Demographic and clinical characteristics of gastric cancer patients in north of Iran, Mazandaran province, 2008-2014

Abstract: Gastric cancer has been known as a poor prognosis disease with a high degree of mortality. In Iran, it has been increased during the previous two decades, especially in northern part of the country. The aim of this study was to determine the demographic and clinical characteristics of gastric cancer in Mazandaran province. All patients with gastric cancer diagnosis treated in the Imam Khomeini educational hospital or Touba Polyclinic, a university affiliated center, from March 2008 to March 2014 were included.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…YG was further divided into two groups, Group A and Group B. Nearly 5-15% of the patients with gastric carcinoma are <40 years and only 1-2% of the patients are <30 years [ 5 , 7 , 8 ]. As reported by Kath et al, the female patient ratio was 75% in gastric cancer patients below the age of 30 years [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…YG was further divided into two groups, Group A and Group B. Nearly 5-15% of the patients with gastric carcinoma are <40 years and only 1-2% of the patients are <30 years [ 5 , 7 , 8 ]. As reported by Kath et al, the female patient ratio was 75% in gastric cancer patients below the age of 30 years [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…The rate of gastric carcinoma has increased in young patients over the past few decades [ 3 , 4 ]. Though gastric carcinoma is rare in young people, it commonly shows a more aggressive biological behavior with a worse prognostic result [ 5 , 6 ]. Nearly 5-15% of the patients with gastric carcinoma are aged <40 years, and only 1-2% of the patients are aged <30 years [ 5 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, this is one of the first studies performed to compare the efficacy and tolerability of most common perioperative chemotherapy regimens in the managing of resectable gastric cancer in the Iranian population. Mousavi et al in 2015 evaluated the efficacy of several most prescribed chemotherapy regimens in resectable and metastatic gastric cancer patients lived in the north of Iran and concluded that the DCF regimen prolonged patients' survival time more than ECF, DOX, and Xeloda -based chemotherapy [48]. Due to a high prevalence of gastric cancer in the countries such as Iran and a lack of definite national and international guidelines to recommend the best therapeutic options [23,48], the necessity of conducting a comparative study among chemotherapeutic regimens is crucial.…”
Section: Discussionmentioning
confidence: 99%
“…[ 5 6 ] Gastric cancer is the most common cancer in men and the second one after breast malignancy in women in Iran and some other countries. [ 7 8 ] It may result in distant metastasis if not treated. [ 9 10 ] In advanced stages, the therapeutic outcomes are poor even after the use of optimal treatment.…”
Section: Introductionmentioning
confidence: 99%